2017
DOI: 10.1097/mpg.0000000000001474
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Marijuana Use in Young Adults With Inflammatory Bowel Disease

Abstract: We found a high rate of marijuana use in our cohort of young adults with IBD. Majority of users report symptom improvement but do not inform physicians. Future well-controlled studies are necessary to assess role of marijuana in IBD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 14 publications
0
48
0
1
Order By: Relevance
“…Studies performed in adults were included as well. By handsearching, we finally included nine studies that evaluate cannabis treatment for adult patients with IBD [2][3][4][5][6][22][23][24][25] and one for adolescent IBD patients (13-21 years of age) [8]. These studies are shown in Table 1.…”
Section: Cannabis Use Among Adult Patients With Ibdmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies performed in adults were included as well. By handsearching, we finally included nine studies that evaluate cannabis treatment for adult patients with IBD [2][3][4][5][6][22][23][24][25] and one for adolescent IBD patients (13-21 years of age) [8]. These studies are shown in Table 1.…”
Section: Cannabis Use Among Adult Patients With Ibdmentioning
confidence: 99%
“…These studies are shown in Table 1. In summary, a high prevalence of cannabis use in adult and adolescent IBD patients is seen in various countries [2][3][4][5][6]. Many patients report beneficial effects of cannabis on IBD-related symptoms, as well as improvement of the quality of life.…”
Section: Cannabis Use Among Adult Patients With Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabis/Cannabinoids in IBD The inflamed gut is highly amenable to treatment with cannabinoids, which is documented for human IBD not only by anecdotal reports but, importantly, also by several questionnaire studies [70][71][72][73] as well as observational studies and prospective clinical trials [74][75][76][77]. Many of the questionnaires have revealed that patients with IBD frequently self-medicate with Cannabis to alleviate abdominal pain and diarrhea.…”
Section: Are Cannabinoids a Therapeutic Option For Inflammation And Nmentioning
confidence: 99%